1989
DOI: 10.1016/0014-5793(89)81591-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Na+, K+ ‐ATPase genes

Abstract: The existence of a chromosome gene family containing at least one gene and one pseudogene was shown for the Na+,K+-ATPase /?-subunit. A partial structure of the pl-gene was determined, the coding part of which was completely homologous to cDNA of the Na+,K+-ATPase /II-subunit from HeLa cells [8]. The region encoding the putative protein transmembrane domain was shown to be bordered by two introns. The structure of a pseudogene (Bv/) was determined. This pseudogene is processed and contains multiple stop codons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We confirmed by sequencing that this was due to unspecific binding of the primers to unrelated sequences. In a single experiment, we found a product and initially classified it as ␤1, but further sequencing identified it as the pseudogene ␤ psi (18). We could never repeat this result, and we ascribe it to contamination by genomic DNA in this single experiment.…”
Section: Figmentioning
confidence: 89%
“…We confirmed by sequencing that this was due to unspecific binding of the primers to unrelated sequences. In a single experiment, we found a product and initially classified it as ␤1, but further sequencing identified it as the pseudogene ␤ psi (18). We could never repeat this result, and we ascribe it to contamination by genomic DNA in this single experiment.…”
Section: Figmentioning
confidence: 89%
“…The discovery of a second type of &subunit leads to the conclusion, that a family of P-subunit genes exists. In fact, when analysing a human genomic library using pig kidney cDNA of the P-subunit as a hybridization probe Ushkaryiov et al found at least two different sequences [86]. One sequence presents most probably the gene coding for P-subunit, the isolated fragment contains one exon coding for the putative transmembrane segment and two introns.…”
Section: The Family Of ~-Subunit Genesmentioning
confidence: 99%
“…The second sequence highly homologous to the pl gene, is intron free and contains many stop codons, and an insert. Therefore it was proposed that this sequence is a pseudogene belonging to the b-subunit family [86].…”
Section: The Family Of ~-Subunit Genesmentioning
confidence: 99%